Poster: A Simple Deep Learning Based V2X Channel Estimation Scheme Using Denoising Autoencoder - Oh, Kang-Hyun; Kim, Chang Hyun; Lim, Sungmook; Song, Changick (IEEE Vehicular Networking Conference, 2024)
To implement the V2X systems, reliable channel estimation is a major critical challenge due to the rapid time-varying characteristic of the vehicular channels. In this recent result paper, we propose a denoising autoencoder (DAE) based channel estimation scheme. The proposed scheme has a simple neural network structure and significantly improves the channel estimation accuracy by training the auto encoder such that it can remove the noise and distortions generated during the data pilot aided channel estimation process. Simulation results verify that the proposed DAE outperforms the conventional deep learning based channel estimation schemes.